2005
DOI: 10.1603/0022-0493-98.6.1863
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Entomopathogenic Nematodes (Steinernematidae) for Control of Overwintering Codling Moth (Lepidoptera: Tortricidae) in Fruit Bins

Abstract: Fruit bins infested with diapausing codling moth larvae, Cydia pomonella (L.), are a potential source of reinfestation of orchards and may jeopardize the success of mating disruption programs and other control strategies. Entomopathogenic nematodes (EPNs) were tested as a potential means of control that could be applied at the time bins are submerged in dump tanks. Diapausing cocooned codling moth larvae in miniature fruit bins were highly susceptible to infective juveniles (IJs) of Steinernema carpocapsae (We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Factors that increase desiccation include high temperatures, low levels of relative humidity, and wind. Although higher temperatures increase the rate of desiccation, nematode activity has proved to increase from 15°C to 32°C (Lacey et al, 2005), and nematodes should be able to reach hosts within a shorter time, when they are exposed to higher temperatures. The exposure time and temperature experiment demonstrated that nematodes were able to infect mealybugs in an exposure time as short as 30 min long at all three temperature levels tested (15°C, 20°C and 25°C), with no significant difference regarding such ability being shown among them.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that increase desiccation include high temperatures, low levels of relative humidity, and wind. Although higher temperatures increase the rate of desiccation, nematode activity has proved to increase from 15°C to 32°C (Lacey et al, 2005), and nematodes should be able to reach hosts within a shorter time, when they are exposed to higher temperatures. The exposure time and temperature experiment demonstrated that nematodes were able to infect mealybugs in an exposure time as short as 30 min long at all three temperature levels tested (15°C, 20°C and 25°C), with no significant difference regarding such ability being shown among them.…”
Section: Discussionmentioning
confidence: 99%
“…Wooden fruit bins used during harvesting and to transport and store fruit have been reported to be infested with diapausing codling moth larvae (Higbee et al 2001). The control of codling moth, using the above-mentioned density-dependent and non-insecticidal practices, can therefore be compromised due to the invasion of orchards by moths emerging from wooden fruit bins which were previously infested and placed in or near orchards prior to harvesting (Cardé and Minks 1995;Higbee et al 2001;Lacey, Neven, Headrick, and Fritts 2005). Bin treatments will thus contribute to lowering the pest population levels and therefore indirectly benefit mating disruption and the sterile insect release programme (Lacey et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cossentine, Jensen, and Moyls (2002) investigated treatment of bins with Steinernema carpocapsae Weiser infective juveniles (IJs) by submersion or drenching, respectively (Weiser 1955). Lacey et al (2005) investigated drenching bins with S. carpocapsae in an industrial bin washer. The use of EPNs to successfully control oriental fruit moth, Grapholita molesta (Busck), in miniature wooden fruit bins has also been documented by Riga, Lacey, Guerra, and Headrick (2006).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve optimum control of codling moth, EPNs have to be applied against the most Influence of humidity and a surfactant-polymer-formulation 783 susceptible stage. Lacey et al (2005) reported that pupae are less susceptible than cocooned last instars, when the insects were exposed to S. carpocapsae at 25°C in perforated cardboard strips fixed to tree trunks in the field. Our findings corroborate these data, however, they reported 63.1 ± 1.7% mortality of pupae with S. carpocapsae, whereas in this study obtained only 4.5% with S. feltiae.…”
Section: Discussionmentioning
confidence: 99%
“…Additives like humectants can help to reduce the negative impact of low RH or low water activity on nematode performance (Baur et al 1995;Lacey et al 2005). We tested the SPF formulation developed by , which not only prolonged survival of the DJs, but also produced favourable environmental conditions for invasion of P. xylostella.…”
Section: Discussionmentioning
confidence: 99%